2017
DOI: 10.1107/s160057671701398x
|View full text |Cite
|
Sign up to set email alerts
|

Variant selection in surface martensite

Abstract: A significant variant selection is reported in isothermal martensite formed on the surface of an Fe-30% Ni sample. The selection phenomenon is modelled using different descriptions of the martensitic phase transformation. In particular, matrices based on the phenomenological theory of martensite crystallography, the Jaswon and Wheeler distortion, and the continuous face centred cubic-body centred cubic distortion are compared. All descriptions allow good predictions of the variant selection. However, the Jaswo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Besides the work presented in this study, we have acquired some EBSD maps on U-bent deformed NiTi alloys. The results confirm the phenomena of variant selection under strain (variant re-orientation), and we will show that they can be interpreted similarly to our previous works on iron alloys [64,65] and AuCu alloys [66]. We have already obtained some EBSD maps showing martensite with equiaxed morphology, which is in good agreement with the hypothesis that the re-orientation between two variants α i → α j is not a "detwinning" operation but a combination of martensite transformations α i → γ → α j .…”
Section: Future Worksupporting
confidence: 90%
“…Besides the work presented in this study, we have acquired some EBSD maps on U-bent deformed NiTi alloys. The results confirm the phenomena of variant selection under strain (variant re-orientation), and we will show that they can be interpreted similarly to our previous works on iron alloys [64,65] and AuCu alloys [66]. We have already obtained some EBSD maps showing martensite with equiaxed morphology, which is in good agreement with the hypothesis that the re-orientation between two variants α i → α j is not a "detwinning" operation but a combination of martensite transformations α i → γ → α j .…”
Section: Future Worksupporting
confidence: 90%
“…Different alloys (stainless steels, iron-nickel and ironnickel-mangenese alloys) exhibit this particular form of martensite [2e4]. Recently, the present authors showed that a natural variant selection takes place in the martensite formed at the surface of Fe-30 wt%Ni alloys [5]. The phenomenon is caused by the presence of the free surface which favours the nucleation of some particular martensite orientations.…”
Section: Introductionmentioning
confidence: 83%
“…The angular power criterion can be understood as a triggering criterion that only takes into account the steric effect of the atoms at the first instants of the distortion process. Baur et al (2017b) showed that this criterion could explain the variant selection of martensite formed at the surface of Fe-Ni alloys during electropolishing. More experimental work on perfectly oriented single crystals is required to compare the predictions based on simple shear (and Schmid's law) with those based on the maximum volume change or on the derivative of the angular distortion.…”
Section: Possible Applications Of the Continuous Distortionmentioning
confidence: 98%
“…The {225} habit plane of martensite in steels could be deduced from the KS OR by relaxing the IPS assumption of the PTMC and by assuming that the interface plane is only untilted (Jaswon & Wheeler, 1948;Cayron, 2015). If required, the {225} unrotated plane can be rendered invariant (IPS) by coupling two KS variants in a twin OR (Baur et al, 2017a). The exact KS OR imposes a strict invariant line along a dense direction that is common to the f.c.c.…”
Section: A2 Some Compatibility Criteria Used In the Ptmcmentioning
confidence: 99%